The late Pleistocene - Holocene sedimentary evolution in the Ba Lat River mouth area of the Red River Delta - Tran Ngoc, Dien; Vu Van, Ha; Paszkowski, Amelie; Nguyen Minh, Quang; Ngo Thi, Dao; Nguyen Thi, Min; Dang Xuan, Tung; Nguyen Chi, Dung; Vu Ngoc, Tuyen; Nguyen Khanh, Tung; et al. (Vietnam Journal of Earth Sciences, 2023)
The Ba Lat estuary is part of the downstream stretch of the Red River Delta, the second-largest Delta in Vietnam and the 12th largest in the world. This study analyses GAT borehole sediments in the Ba Lat estuary area to assess environmental changes during the Late Pleistocene - Holocene period. This entailed detailed analyses of 70 m-deep borehole data from the Ba Lat estuary area, including structural analysis of 70 m-deep sediment core samples, 230 samples of grain size, 49 samples of Foraminifera, five samples of petrographic thin slices, and four samples of radiocarbon dating. The data reveal nine sedimentary facies, including river channel sand facies, floodplain clayey silt facies, tidal flat sandy-silty facies, bay clayey silt facies, pro-delta clayey silt facies, delta front sandy-silty clay facies, mouth bar sand facies, tidal flat sandy - silty clay facies, and delta plain silty clay facies. The combined nine sedimentary facies formed sequentially in time, representing the evolution of the sedimentary environment from the Late Pleistocene to the Holocene and the evolutionary process from the continental to the estuarine and Delta environment. The results also enable the geographic identification and delineation of the incised valley in the Red River Delta during the Late Pleistocene to Holocene period. The sedimentation rate in the incised valley varies from period to period. In the sedimentation phase of the incised valley, the average accretion rate reached 11.64 mm/year. In contrast, during the open sea regime (shallow sea near the coast), the accretion rate was observed to be very low, with a rate of 1.27 mm/year and the period of delta formation had the highest accretion rate, reaching 13.41 mm/year.